Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I did it with using truth tables but I am inquisitive about how to proof the distributive property without using truth tables (i.e using the other rules of replacement or inference).

$$ (P \land (Q \lor R)) \Leftrightarrow ((P \land Q) \lor (P \land R))$$


$$ (P \lor (Q \land R)) \Leftrightarrow ((P \lor Q) \land (P \lor R)) $$

share|cite|improve this question
up vote 4 down vote accepted

Here's a hint how you might start constructing a proof of the first biconditional in a standard natural deduction system.

You need to prove the two halves of the conditional separately. So, to go left to right, assume the antecedent $(P \land (Q \lor R))$ and aim for the consequent $(P \land (Q \lor R)) \to ((P \land Q) \lor (P \land R))$. Plainly you need to extract the two conjuncts $P$ and $(Q \lor R)$ from your assumption. And now obviously the only way forward is to use $\lor$-elimination.

So you now need to fill in the following schematic proof:

$\quad|\quad(P \land (Q \lor R)) \quad\quad\text{assumption}\\ \quad|\quad P \\ \quad|\quad(Q \lor R))\\ \quad|\quad|\quad Q \quad\quad\quad\quad\quad\text{ assumption}\\ \quad|\quad|\quad ...\\ \quad|\quad|\quad ((P \land Q) \lor (P \land R))\\ \quad|\quad|\quad --\\ \quad|\quad|\quad R\quad\quad\quad\quad\quad\text{ assumption}\\ \quad|\quad|\quad ...\\ \quad|\quad|\quad ((P \land Q) \lor (P \land R))\\ \quad|\quad ((P \land Q) \lor (P \land R))\quad\text{ by or-elimination, discharging assumptions}\ Q,\ R\\ \quad (P \land (Q \lor R)) \to ((P \land Q) \lor (P \land R)) \quad\text{by conditional proof}\\ $

Do you see understand this sort of proof strategy? Do you see how to fill in the gaps??

If you do, then you'll easily be able to produce similar proofs for the reverse conditional, and likewise for the two halves of your other biconditional.

If you don't, then have a look e.g. at Paul Teller's Formal Logic Primer, freely available online.

share|cite|improve this answer
I can understand $P$ and $(Q \lor R) $ via [simplification]( on $(P \land (Q \lor R))$. However I am not sure how $Q$ is followed?! – Quixotic Oct 27 '12 at 18:09
It doesn't follow. it is a new supposition. Check out how or-elimination works in ND. – Peter Smith Oct 27 '12 at 18:28

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.